2023
DOI: 10.1177/02698811231209194
|View full text |Cite
|
Sign up to set email alerts
|

The psychedelic effects of cannabis: A review of the literature

David Wolinsky,
Frederick Streeter Barrett,
Ryan Vandrey

Abstract: Cannabis and classic psychedelics are controlled substances with emerging evidence of efficacy in the treatment of a variety of psychiatric illnesses. Cannabis has largely not been regarded as having psychedelic effects in contemporary literature, despite many examples of historical use along with classic psychedelics to attain altered states of consciousness. Research into the “psychedelic” effects of cannabis, and delta-9-tetrahydrocannabinol (THC) in particular, could prove helpful for assessing potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Further, we were also unable to match groups in terms of the frequency of cannabis use. Cannabis and THC are known to induce robust altered states of consciousness, including experiences of oceanic boundlessness, ego-dissolution, and disembodiment (Zaytseva et al, 2019;Murray & Srinivasa-Desikan, 2022;Murray et al, 2024;Wolinsky et al, 2023). Therefore, in order to control for the confounding effect of both meditation practice and cannabis use, we employed a statistical weighting approach that reduced the impact of data from participants with extensive meditation experience and history of cannabis use (similarly to our previous study in the same cohort; Orłowski et al, 2023).…”
Section: Methodological Aspects and Limitationsmentioning
confidence: 99%
“…Further, we were also unable to match groups in terms of the frequency of cannabis use. Cannabis and THC are known to induce robust altered states of consciousness, including experiences of oceanic boundlessness, ego-dissolution, and disembodiment (Zaytseva et al, 2019;Murray & Srinivasa-Desikan, 2022;Murray et al, 2024;Wolinsky et al, 2023). Therefore, in order to control for the confounding effect of both meditation practice and cannabis use, we employed a statistical weighting approach that reduced the impact of data from participants with extensive meditation experience and history of cannabis use (similarly to our previous study in the same cohort; Orłowski et al, 2023).…”
Section: Methodological Aspects and Limitationsmentioning
confidence: 99%
“…Over 30 million people in the United States have consumed classic psychedelics, such as psilocybin, LSD, or mescaline ( Krebs & Johansen, 2013 ). Research suggests some other substances also produce similar hallucinogenic effects and considered as atypical psychedelics, such as marijuana/cannabis ( Wolinsky et al, 2024 ). Further, it is evidenced that some antidepressants, such as St John’s wort ( Ferrara et al, 2017 ; Gurok et al, 2014 ) and Fluoxetine ( Webb & Cranswick, 2003 ), and some tranquilizers ( Kadriu et al, 2021 ) also produce some hallucinogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that classic psychedelics (e.g., psilocybin and LSD) and atypical psychedelics (e.g., cannabis) may be useful in treating mental and neurocognitive disorders due to their ability to stimulate neurogenesis, produce neuroplastic changes, and reduce neuroinflammation ( Vann Jones & O’Kelly, 2020 ; Vollenweider & Preller, 2020 ; Wolinsky et al, 2024 ). Neuroinflammation is significantly associated with the development of Alzheimer’s disease and is considered the most common form of dementia ( F. Zhang & Jiang, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis and MDMA are not traditionally classified as classic hallucinogens; however, they share some pharmacological properties and mechanisms of action with hallucinogenic substances. Endogenous cannabinoids have been found to modulate serotonin, gamma-aminobutyric acid, and glutamate release [ 19 ], whereas MDMA releases serotonin from presynaptic 5-HT terminals and is a potent releaser of dopamine and noradrenaline [ 20 ]. While there is no consensus upon a classification of cognitive functions, a proposed taxonomy categorizes cognition with emotional valence as “hot cognition” (e.g., anhedonia, negativistic rumination), which differs from “cold cognition” (e.g., learning, memory, executive function, information processing speed, attention/concentration) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%